Zadania edukacyjno-pastoralne we współczesnych szkołach katolickich na przykładzie szkolnictwa salezjańskiego - Wierzbicki, Mirosław Stanisław (Studia Pastoralne, 2026)
This article talks about an educational and pastoral tasks in Catholic schools on the example of the Salesian education. These tasks are assigned to specific individuals who run schools and form their Catholic character. The school is in fact for all – teachers and students – a community of generations, a great educational family in which every young person meets with respect, regardless of their ability and intellectual capacity. Therefore we analyze the current social situation of young people and education, in order to show that the tasks arising from the ministerial, Church documents and the needs of the environment require continuous evaluation and adaptation to current conditions of national, youth, family and school development.